MANAJEMEN PEMBIAYAAN PENDIDIKAN PPDB DI MTs ASSALAAM BANDUNG - Ardiansyah, Ardiansyah; Muzakki, Ahsyaf; Hidayat, Ara (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
Education at Madrasah Tsanawiyah (MTs) has an important role in producing a generation that excels both academically and in Islamic character. In the process of providing education, effective financing management, especially in Admission of New Students (PPDB), is a crucial factor. This research aims to analyze PPDB financing management at MTs Assalam Bandung, identify obstacles and opportunities in the management process, and propose improvement strategies to increase financing efficiency. The research used a qualitative approach with a case study method, involving interviews with madrasa heads, financial staff, the PPDB committee, and analysis of financial documents. The research results show that PPDB financing management at MTs Assalam Bandung is carried out through detailed planning, efficient management and strict supervision. The use of a wave-based payment system and online registration increases operational efficiency and transparency. However, challenges such as late payments and parents' lack of understanding of financial provisions are still the main obstacles. The resulting recommendations include implementing an installment and education savings system, as well as strengthening communication between schools and parents to ensure a better understanding of financial regulations. This research concludes that transparent and efficient financing management can improve the quality of education and build public trust in educational institutions.